A quick in vitro pathway from prokaryotic genomic libraries to enzyme discovery - Lyubov A. Ryabova; Sabrina Guillemer; Stéphanie Pallas; Cécile Persillon; Fabrice Lefèvre; Jean-Michel Masson; Gilles Ravot (BioTechniques)
Screening of prokaryotic genomes in order to identify enzymes with a desired catalytic activity can be performed in vivo in bacterial cells. We propose a strategy of in vitro expression screening of large prokaryotic genomic libraries based on Escherichia coli cell-free transcription-translation systems. Because cell-based expression may be limited by poor yield or protein misfolding, cell-free expression systems may be advantageous in permitting a more comprehensive screen under conditions optimized for the desired enzyme activity. However, monocistronic messages with an improved leader initiation context are typically used for protein production in vitro. Here, we describe successful use of a Pseudoalteromonas genomic DNA library for in vitro expression of DNA fragments carrying multiple open reading frames (ORFs) in the context of their authentic translation initiation sites and regulatory regions. We show that ORFs located far from the 5′ and 3′ ends of polycistronic transcripts can be expressed at a sufficient level in an in vitro transcription-translation system in order to allow functional screening. We demonstrate the overall cell-free functional screen strategy with the successful selection of an esterase from Pseudoalteromonas.